From Service to Success New Mission, New Purpose, and a New Journey to a Great Life - Taylor, Bob (Morgan James Publishing, 2023)
From Service to Success offers a roadmap for veterans seeking to adjust to civilian life and move beyond the trauma of active service to discover their greatest season of life yet!